AVAILABLE EDUCATIONAL TOOLS AND METHODS FOR CAREGIVERS OF INFANTS AND YOUNG CHILDREN FOR DEMONSTRATING COMPETENCE ON CPR: A SCOPING REVIEW - Michail, Koralia; Tsoukala, Dionysia; Petsios, Konstantinos (My University, 2025)
Background and aims: Out-Hospital Cardiac Arrest (OHCA) outcomes differ, according to the timely initiation of CPR. Delayed initiation has been associated with poor neurological outcomes, whereas when a bystander is present, higher rates of ROSC and better outcomes have been observed. Caregivers of children, often serve as first responders. Thus, it is important for caregivers to be able to act and have competence in resuscitation skills. This scoping review aims to gather available educational tools and methods, providing retained competency on CPR skills for caregivers of young children. Methods: A scoping review was implemented, guided by the PRISMA (ScR) guidelines. Embase, CINAHL, Web of Science and Pubmed, were systematically searched from inception until December 2024. COVIDENCE was used for articles screening, assessment of eligibility and data extraction. Results: The search yielded 23 from a total of 590 articles from all databases. Three topics emerged concerning the educational methods: self-directed learning, stimulation-based learning / instructor-led learning and blended learning. Caregivers appeared satisfied and retained knowledge when simulation-based learning / instructor-led learning was used, whilst all forms of training appeared to decrease their anxiety and positively affect their self-confidence to perform CPR. Conclusions: Caregivers’ CPR training enhances preserved knowledge and alleviates parental anxiety, particularly for parents of children with pre-existing medical conditions, while enabling them with the necessary self-efficacy to act as rescuers during emergencies. The advancement of new educational technologies and methods including Virtual Reality and simulation-based learning can pave the way for new research on caregivers’ retained skills.
Keywords: Pediatric Nursing; CPR; educational tools; Scoping review